Gastric Damage and Cancer-Associated Biomarkers in Helicobacter pylori-Infected Children - George, Sergio; Lucero, Yalda; Torres, Juan Pablo; Lagomarcino, Anne J.; O’Ryan, Miguel (Frontiers in Microbiology, 2020)
Helicobacter pylori (H. pylori) is well-known to be involved in gastric carcinogenesis, associated with deregulation of cell proliferation and epigenetic changes in cancer-related genes. H. pylori infection is largely acquired during childhood, persisting long-term in about half of infected individuals, a subset of whom will go on to develop peptic ulcer disease and eventually gastric cancer; however, the sequence of events leading to disease is not completely understood. Knowledge on carcinogenesis and gastric damage-related biomarkers is abundant in adult populations, but scarce in children. We performed an extensive literature review focusing on gastric cancer related biomarkers identified in adult populations, which have been detected in children infected with H. pylori. Biomarkers were related to expression levels (RNA or protein) and/or methylation levels (DNA) in gastric tissue or blood of infected children as compared to non-infected controls. In this review we identified 37 biomarkers of which twenty-four are over expressed, three are under expressed, and ten genes are significantly hypermethylated in H. pylori-infected children compared to healthy controls in at least 1 study. Only 4 of these biomarkers (pepsinogen I, pepsinogen II, gastrin and SLC5A8) have been studied in asymptomatically infected children. Importantly, 13 of these biomarkers (β-catenin, C-MYC, GATA-4, DAPK1, CXCL13, DC-SIGN, TIMP3, EGFR, GRIN2B, PIM2, SLC5A8, CDH1 and VCAM-1.) are consistently deregulated in infected children and in adults with gastric cancer. Future studies should be designed to determine the clinical significance of these changes in infection-associated biomarkers in children and their persistence over time. The effect of eradication therapy over these biomarkers in children if proven significant, could lead to modifications in treatment guidelines for younger populations, and eventually promote the development of preventive strategies, such as vaccination, in the near future.